Strong Equivalence Principle: Violations without Failure a PPN Classroom Framework with a Brans–Dicke Counterexample - Cody, Michael Aaron (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The study aims to clarify that the Strong Equivalence Principle (SEP) is sufficient but not necessary for reproducing classical solar-system tests of gravity. The framework targets persistent student misconceptions, offering instructors a concise way to separate principles from observations. Methodology: The analysis applies the standard parametrized post-Newtonian (PPN) formalism focusing on parameters γ and β. Worked examples from Brans–Dicke theory illustrate explicit predictions when γ ≠ 1. A concise three-stage instructional sequence, introducing γ and β, analyzing the Brans–Dicke counterexample, and interpreting the resulting parameter-space diagram, serves as the pedagogical intervention guiding students in distinguishing sufficiency from necessity within gravitational theory. Main Findings: Results confirm that SEP enforces γ=β=1, while experimental constraints allow small deviations. Brans–Dicke theory with finite coupling demonstrates that SEP violations can still pass key solar-system tests: light deflection, Shapiro delay, and perihelion advance. Classroom diagrams and exercises show students how alternative theories succeed observationally, even when SEP is not strictly satisfied, thereby correcting misconceptions. Novelty/Originality of this study: The study reframes established theoretical results into a compact pedagogical tool. Unlike prior treatments that present SEP as both sufficient and necessary, this approach emphasizes the logical distinction and demonstrates it with concrete counterexamples. Its originality lies in providing classroom-ready illustrations and tasks, equipping instructors to teach SEP more accurately and address misconceptions effectively.